Comprehensive Laboratory Evaluations and a Proposed Mix Design Procedure for Cement-Stabilized Cohesive and Granular Soils - Yang, Yi; Li, Shengting; Li, Cheng; Wu, Lijian; Yang, Lvzhen; Zhang, Ping; Huang, Tuo (Frontiers in Materials, 2020)
Embankment subgrade soils classifying as A-4 to A-7-6 according to the AASHTO Soil Classification System can exhibit low bearing strength, high volumetric instability, and freeze-thaw susceptibility. These characteristics of soil are frequently identified as main factors leading to accelerated damage of pavement systems. Cement stabilization has been widely used to improve these soils conditions. The present study aims to help designers and practioners better understand how cement stabilizations can influence soil index properties and mechanical properties before and after saturation. In this study, a total of 28 cohesive and granular soil materials obtained from 9 construction sites were tested using 4 to 12% type I/II Portland cement contents. Specimens were prepared using a 2 in. by 2 in. compaction apparatus and tested for 28-day unconfined compressive strength with and without vacuum saturation. Results indicated that statistically significant relationships exist between soil index properties, unconfined compressive strength, and cement content. Based on the laboratory test results, a laboratory evaluation procedure for cement stabilization mix design for both granular and cohesive soils is proposed.